The Effect of Resveratrol on Cellular Senescence in Normal and Cancer Cells: Focusing on Cancer and Age-Related Diseases. (3rd October 2019) - Farhadnejad, Hossein; Emamat, Hadi; Zand, Hamid
Abstract: Cellular senescence is generally defined as irreversible cell-cycle arrest and loss of replicative capacity in virtually all cell types which can have effects on tissues and possibly play a significant role in promoting age-related chronic diseases and cancers. Recently, use of natural bioactive substances such as resveratrol to modify the process of cellular senescence in tissue cells based on specific context has opened an interesting therapeutic perspective in aging and chronic diseases such as cancers. This natural polyphenol is currently being evaluated as a promising anticancer and anti-age-related disease agent. Resveratrol modulates cell cycles and multiple pathways involved in cell growth, apoptosis, senescence, and inflammation, which has mostly observed in laboratory models. In vitro studies indicate that biological effects of resveratrol on cellular senescence or other cell processes may vary depending on cell types and certain contexts. This review aims to discuss the current body of knowledge on the effects of resveratrol on cellular senescence in cancerous and normal cells and its possible effect on prevention of cancers and aging based on in vitro and in vivo studies. It also deals with the putative mechanisms underlying these effects of resveratrol and propounds the controversy on this topic.